2022
DOI: 10.1142/s0217595922500051
|View full text |Cite
|
Sign up to set email alerts
|

Slack Due-Window Assignment Scheduling Problem with Deterioration Effects and a Deteriorating Maintenance Activity

Abstract: This paper studies the slack due-window assignment scheduling problem with deterioration effects and a deterioration maintenance activity on a single-machine. The machine deteriorates during the machining process, and at a certain moment performs a deterioration maintenance activity, that is, the duration time of the maintenance activity is a linear function of the maintenance starting time. It is needed to make a decision on when to schedule the deteriorating maintenance activity, the optimal common flow allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They also showed that some special cases of the problem are polynomially solvable. Jia et al [24] and Sun et al [25] considered single machine scheduling with deteriorating jobs and a maintenance activity. Miao et al [26] investigated single machine scheduling with deteriorating jobs and delivery times.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that some special cases of the problem are polynomially solvable. Jia et al [24] and Sun et al [25] considered single machine scheduling with deteriorating jobs and a maintenance activity. Miao et al [26] investigated single machine scheduling with deteriorating jobs and delivery times.…”
Section: Introductionmentioning
confidence: 99%
“…For the three versions of scheduling cost and resource consumption cost, they proved that the problem can be solved in polynomial time. Jia et al [17] discussed the combination of the SLKDW and deterioration effects. Lv and Wang [18] researched the two-machine flowshop scheduling with the DIFDW and resource allocation.…”
Section: Introductionmentioning
confidence: 99%